Assessing the Best Supplier Selection Criteria in Supply Chain Management During the COVID-19 Pandemic - Hou, Yumei; Khokhar, Maryam; Zia, Sayma; Sharma, Anshuman (Frontiers in Psychology, 2022)
In the last ten years, organisations and Rresearchers have recognised the importance of sustainable supply chain management (SSCM) because of the consumers, or-profit and non-profit organisations, laws and regulations, and consumer social and corporate responsibilities. Supplier selection, environmental effects such as social cooperation, and other SSCM programmes, all can help to achieve the "triple bottom line (TBL)" of economic, environmental, and social advantages. Sustainable supplier selection (SSS) and firm performance are important factors in supply chain management (SCM). Organizations will traditionally consider a new framework when evaluating SSS performance to obtain all-encompassing criteria/sub-criteria of the sustainability index by encapsulating sustainability. This paper compiles 12 sub-criteria for three sustainability pillars. Economic, environmental, and social performance. Despite the fact that many articles on SSS and evaluation were published during COVID-19, there seems to be little research on sustainability issues to date. The goal of this study is to suggest a fuzzy multi-criteria approach to SSCM planning. Additionally, using the TBL method, investigate the problem of determining a current model for SSS in the supply chain. The linguistic value of the subjective preference of experts is represented by triangular fuzzy numbers. Fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) is proposed to use standard weights to rank SSS for qualitative performance evaluation. COVID-19, on the other hand, has a detrimental impact on SSS and company results. The organization's performance suffers as a result of the COVID-19 shutdown. The proposed method is demonstrated using an example.